The Influence of a Prevention Education Program for High-Risk Sexual Behaviors on Sexual Knowledge and Sexual Attitude of Female undergraduate Students - Elnaz Dehghani; Fatemeh Erfanian Arghavanian; Talat Khadivzadeh; Mohammad Taghi Shakeri (Mashhad University of Medical Sciences, 2022)
Background & aim: Prevention of high-risk sexual behaviors due to its prevalence among young people is an important health concern. Because of the importance of promoting young people` sexual health, the present study was conducted to investigate the effect of training high-risk sexual behaviors prevention through an educational package on sexual knowledge and attitude of students.Methods: This quasi-experimental study with a two-group pretest-posttest design was performed on 200 eligible female undergraduate students of Mashhad University of Medical Sciences, Mashhad, Iran in 2016. The subjects were randomly divided into two groups of intervention and control group. In the intervention group, the participants received a prevention education program through a training package. Students' sexual knowledge and attitude were assessed using self-structured sexual knowledge and attitude questionnaires before and two weeks after the training. Paired and independent t-test, Mann-Whitney, Wilcoxon and Chi-square tests was used to analyze data by SPSS (version 16).Results: Sexual knowledge mean score of intervention group was significantly higher compared to the control group (29.29±1.14 vs 14.41±4.21, P=0.005) after training. Mean score of students' sexual attitude although increased after training in intervention group compared to the control group (139.39±13.17 vs 133.01±9.79), but this difference was not significant (P=0.081).Conclusion: The students` sexual knowledge was increased through using sexual training package as prevention education program. This method is recommended for sexual education and counseling of students to prevent high-risk sexual behaviors and promote community health.